Design and Sustainability – The case and practice for a sustainability designer - Galloway, David John (Curtin University, 2014)
The case for linking sustainability and design is explored and a new profession of sustainability designer posited. A conceptual underpinning for the praxis is identified as resolving wicked problems. Philosopher Paul Ricoeur’s description of narrative identity is seen as an alternative to the modernist roots of wicked problems. A praxis based in narrative identity is examined through case studies about: personal engagement and design practice, narrative, right to intervene, leadership, creating physicalities, and working forums.